2020
DOI: 10.3390/molecules25071615
|View full text |Cite
|
Sign up to set email alerts
|

Role of Indole Scaffolds as Pharmacophores in the Development of Anti-Lung Cancer Agents

Abstract: Lung cancer is the leading cause of death in men and women worldwide, affecting millions of people. Between the two types of lung cancers, non-small cell lung cancer (NSCLC) is more common than small cell lung cancer (SCLC). Besides surgery and radiotherapy, chemotherapy is the most important method of treatment for lung cancer. Indole scaffold is considered one of the most privileged scaffolds in heterocyclic chemistry. Indole may serve as an effective probe for the development of new drug candidates against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 107 publications
(187 reference statements)
0
60
0
Order By: Relevance
“…Of the numerous halogenases, the flavin-dependent halogenases (FDHs) have been a focus for biotechnologists, due to their high substrate-and regio-specificity, and their ability to function independently of carrier proteins that bind the substrate. A subgroup of FDHs targeting the indole moiety of tryptophan are the most well studied group of FDHs, due to the prevalence of indole as a building block in both biology and synthetic chemistry (Frese and Sewald, 2015;Dhuguru and Skouta, 2020). Mechanistically, these tryptophan halogenases are similar to haem-dependent haloperoxidases and vanadiumdependent haloperoxidases in that they form a hypohalous acid (HOX) intermediate.…”
Section: Halogenation In Nature and Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…Of the numerous halogenases, the flavin-dependent halogenases (FDHs) have been a focus for biotechnologists, due to their high substrate-and regio-specificity, and their ability to function independently of carrier proteins that bind the substrate. A subgroup of FDHs targeting the indole moiety of tryptophan are the most well studied group of FDHs, due to the prevalence of indole as a building block in both biology and synthetic chemistry (Frese and Sewald, 2015;Dhuguru and Skouta, 2020). Mechanistically, these tryptophan halogenases are similar to haem-dependent haloperoxidases and vanadiumdependent haloperoxidases in that they form a hypohalous acid (HOX) intermediate.…”
Section: Halogenation In Nature and Pharmacologymentioning
confidence: 99%
“…They therefore allowed the halogenases to target tryptophan and expressed an E. coli-derived tryptophanase (TnaA) to convert this into a halogenated indole, which could then be converted, with varying efficiencies, to chloro-indican in planta. As indole is a common biosynthetic precursor, and a privileged heterocyclic scaffold (Dhuguru and Skouta, 2020), this system may help to unlock derivative space surrounding a number of diverse metabolites.…”
Section: Kong Et Al 2020mentioning
confidence: 99%
“…In the metaphysical healing concept, Spirtualism concepts like prayers, invocations, or incantations have been offered to some mysterious and powerful forces in the various belief concept system like exorcism, divination, libation etc., were also been practicing to heal several diseases, how ever, scientific validation and documentation is still challenging [5,6]. Some of plants used in herbalism by traditional african healers are Foeniculum vulgare Mill [7], Rauvolfia serpentina Linn [8], Cinchona pubescens Vahl [9], Digitalis purpurea Linn [10], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, two marketed RTK inhibitors, sunitinib and osimertinib, possess an indole core. Sunitinib, a PDGFR and VEGFR inhibitor, was approved in the treatment of renal cell carcinoma and gastrointestinal stromal tumor, whereas osimertinib, an EGFR inhibitor, was approved in the treatment of NSCLC [38][39][40]. On the other hand, it was also demonstrated that indomethacin, an indole-based COX-1 and COX-2 inhibitor, exhibited anti-lung cancer and anti-CRC activity through chemical modifications on the main structure [41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%